1957
DOI: 10.3181/00379727-95-23232
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosal Erosion in the Rat Following Administration of the Serotonin Precursor, 5-Hydroxytryptophan

Abstract: Plrariiracolog~, S n t i o r i d Heart Zitst it r ( t t 3 , S . I .W ., Bet hasda, Maryland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

1959
1959
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 4 publications
0
15
1
1
Order By: Relevance
“…However, the degree of acid back diffusion caused by aspirin in sympathectomized rats was found to be the same as that in sham operated animals. The pathogenesis of serotonin-induced ulcers has been reported (15,16), but such remains to be fully elucidated. Aures and Thompson (17) observed that serotonin contents were decreased in the stomach of immunosympathectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of acid back diffusion caused by aspirin in sympathectomized rats was found to be the same as that in sham operated animals. The pathogenesis of serotonin-induced ulcers has been reported (15,16), but such remains to be fully elucidated. Aures and Thompson (17) observed that serotonin contents were decreased in the stomach of immunosympathectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…of the injection of large doses of 5-hydroxytryptophan. Reserpine in large doses had a similar effect (Benditt and Wong, 1957;Haverback and Bogdanski, 1957;Blackman, Campion, and Fastier, 1958). Some of the pharmacological actions of both these drugs appear to be mediated by 5-hydroxytryptamine.…”
mentioning
confidence: 86%
“…Other workers (Wilhelmi, 1957;Hedinger and Veraguth, 1957) have shown that 5-hydroxytryptamine in large doses causes gastric ulceration in the rat. The 5-hydroxytryptamine precursor, 5-hydroxytryptophan, has also been shown to produce gastric mucosal erosion in the rat (Haverback and Bogdanski, 1957). Haverback and Bogdanski (1957) observed that lesions after the administration of 5-hydroxytryptophan were fewer or even absent if the rats had been atropinized.…”
Section: Effect Of Iproniazidmentioning
confidence: 99%
See 1 more Smart Citation
“…Haverback and Bogdanski (10) reported that serotonin administered to rats in a dose of 300 mg/kg produced haemorrhagic mucosal erosions in the glandular por tion of the stomach and formation of these lesions was prevented by pretreatment with atropine sulfate. Blackman et al (11) also reported that serotonin as well as reserpine caused gastric haemorrhages in normal mice but not in the vagotomized mice and they concluded that reserpine-like drugs caused gastric haemorrhage by a mechanism which involved the liberation of central monoamines.…”
Section: Effects Of Dibenamine and Atropine A) Dibenaminementioning
confidence: 99%